Vladimir Horowitz plays Mozart a recording session of Mozart's Piano concerto no. 23 - Mozart, Wolfgang Amadeus 1756-1791 (CAMI Video Inc., 1988)
Legendary pianist Vladimir Horowitz, conductor Carlo Maria Giulini and The Orchestra of La Scala perform Mozart's Piano Concerto No. 23 in A Major, K. 488. Born in Kiev in 1903, Vladimir Horowitz soon acquired an international fame for his renditions of the Romantic repertoire and his incredible virtuosity. Nicknamed the "Titan of the Piano," "Satan on the Keyboard" or "The King of the Piano," Vladimir Horowitz left an imperishable mark on the public's mind and was admired by all his peers, including Clara Haskil, Martha Argerich, Sviatoslav Richter, to name but a few. Accompanied by The Orchestra of La Scala conducted by Carlo Maria Giulini (another titan of the 20th century) that Vladimir Horowitz performs Mozart's Piano Concerto No. 23 in A Major, K. 488 in a studio setting. The film also includes discussions, playback sessions and interviews with the maestro